2020
DOI: 10.1177/0735633120927489
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality for Early Language Learning: A Systematic Review of Augmented Reality Application Design, Instructional Strategies, and Evaluation Outcomes

Abstract: In this article, we present a systematic review of literature on augmented reality (AR) supported for early language learning. We analyzed a total of 53 papers from 2010 to 2019 using qualitative analysis with complementary descriptive quantitative analysis. Our findings revealed three main AR learning activities: word spelling games, word knowledge activities, and location-based word activities. Our findings also uncovered five main design strategies: three-dimensional multimedia content, hands-on interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 90 publications
1
34
0
1
Order By: Relevance
“…Computer game-assisted teaching could produce significantly better learning outcomes than non-computer game-assisted teaching. Augmented computer games could lead to significantly better learning outcomes than standard games (Fan et al, 2020). Game mechanics characteristics, visual and narrative characteristics, and research quality characteristics could greatly influence learning outcomes, which indicated that the design of games played a key role in learning (Clark et al, 2016).…”
Section: Rq1: Could Learning Outcomes Be Greatly Improved In Educational Game-based Learning?mentioning
confidence: 99%
“…Computer game-assisted teaching could produce significantly better learning outcomes than non-computer game-assisted teaching. Augmented computer games could lead to significantly better learning outcomes than standard games (Fan et al, 2020). Game mechanics characteristics, visual and narrative characteristics, and research quality characteristics could greatly influence learning outcomes, which indicated that the design of games played a key role in learning (Clark et al, 2016).…”
Section: Rq1: Could Learning Outcomes Be Greatly Improved In Educational Game-based Learning?mentioning
confidence: 99%
“…Students using AR game had a "superior English learning progress" than the control group using traditional methods (Barreira et al, 2012). Interestingly, a study revealed that academically good students did not show a sign of improvement but students with lower academic success showed a greater improvement in ARsupported lessons (Freitas & Campos, 2008). In Freitas & Campos' (2008) study conducted with 2nd grade primary school students, SMART AR system, an educational system employing AR for teaching concepts, had notable impact on the whole class collaboration.…”
Section: Content Retentionmentioning
confidence: 99%
“…The learning theory to be embraced depends on the kind of instructional strategy to be used. Upon reviewing the related literature, Fan et al (2020) groups these AR-based instructional strategies into three, namely, "instruction through presentation (i.e., teacher-centered informal instruction), instruction through discovery (i.e., learner-centered comprehensive instruction), and collaborative learning (i.e., learner-centered group studies)".…”
Section: Learning Theoriesmentioning
confidence: 99%
“…Antle, J.L. Warren draw attention to psychological factors and risks of using new digital tools in terms of supporting personality development (Fan et al, 2020). Indeed, along with the undoubted didactic potential, information technologies for teaching, upbringing, and personal development, the impending danger that the digital school teacher should see and understand should be highlighted.…”
Section: Relevance 21 Analysis Of Russian Scientific and Pedagogical Literaturementioning
confidence: 99%
“…Antle, J.L. Warren point out: balance and feasibility of using innovative technologies to support cognitive activity when solving practice-oriented tasks, project management, and organization of teamwork are important (Fan et al, 2020).…”
mentioning
confidence: 99%